Identification of platelet function-related genes in STEMI patients - Zhu, Jingjing; Yang, Shuangya; Guo, Qing; Yang, Yifan; Shi, Bei (Frontiers in Genetics, 2025)
BackgroundST-elevation myocardial infarction (STEMI) is characterized by extensive myocardial necrosis due to acute and severe ischemia, with platelets playing a key role in its pathogenesis. This study aimed to identify platelet function-related biomarkers in STEMI patients.MethodsThe GSE59867 dataset, including STEMI patients and controls, was analyzed to identify differentially expressed genes (DEGs) using the limma R package. Platelet function-related DEGs (DEPRGs) were obtained by intersecting DEGs with platelet-related genes. Gene ontology (GO) and kyoto encyclopedia of genes and genomes (KEGG) enrichment analyses were performed, and a protein-protein interaction (PPI) network was constructed using STRING, followed by identification of hub genes via Cytohubba. The diagnostic value of these genes was evaluated through receiver operating characteristic (ROC) analysis, and further expression validation along with ROC validation was conducted in the GSE123342 dataset. Additionally, gene expression was validated by quantitative real-time polymerase chain reaction (RT-qPCR) in peripheral blood from STEMI patients and cardiac tissue from STEMI mouse models.ResultsA total of 245 DEPRGs were identified; enrichment analyses revealed their primary involvement in hemostasis, coagulation, and platelet activation (adjusted P < 0.05). The PPI network screening identified 11 hub genes, among which GRB2, MAPK1 (ERK2), MAPK3 (ERK1), PIK3CA, AKT1, and PIK3R1 demonstrated strong diagnostic performance (AUC > 0.7). ROC analysis yielded the following AUC values (95% CI): GRB2 0.759 (0.678–0.835), MAPK1 0.736 (0.650–0.810), MAPK3 0.824 (0.752–0.885), PIK3CA 0.806 (0.735–0.868), AKT1 0.724 (0.633–0.807), and PIK3R1 0.809 (0.732–0.879); all P-values were <0.05 after adjustment for multiple comparisons. Further validation in an independent dataset confirmed that MAPK3 (P = 1.6 × 10−5) and GRB2 (P = 8.2 × 10−7) exhibited consistent expression trends with the training set, with ROC analysis showing AUC values greater than 0.7 for both genes (MAPK3: AUC = 0.808 [95% CI: 0.709–0.899]; GRB2: 0.759 AUC = [95% CI: 0.765–0.929]). Thus, MAPK3 and GRB2 were identified as key genes. qPCR validation in peripheral blood from STEMI patients (n = 30) and cardiac tissue from a mouse myocardial infarction model further confirmed the differential expression of GRB2 and MAPK3 (P < 0.05).ConclusionThis study identified two platelet function-related genes, MAPK3 and GRB2, as potential biomarkers for STEMI, demonstrating high clinical relevance and diagnostic value.